STRATEGI PEMERINTAH DAERAH GUNA MEWUJUDKAN NILAI-NILAI MULTIKULTURALISME DALAM PERSPEKTIF KETAHANAN WILAYAH (Studi Kasus Di Daerah Istimewa Yogyakarta) - Herlambang, Purnomo (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
Abstract – The values of multiculturalism in Indonesia were born along with the awareness of the nation’s children to expel the invaders from ths archipelago with the spirit of togetherness, sharing the same fate, and the desire to leave regional traits that have been proven unable to expel the invaders from this motherland. It ie from this spirit of togetherness rooted in diversity that brings the Indonesian people to gates of Indonesian. Independence, United, sovereign, just and prosperous. The spirit of multiculturalism values that are still being guided by all Indonesian people are the value of mutual respect, the value of mutual tplerance, the value of unity, the value of cooperation, and the value of solidarity that must be nurtured ang maintaied. The Special Region of Yogyakarta is part of the unity state of the Republic of Indonesia, which has an attarction for the Indonesian people themselves ang the world community to visit and get to know Yogyakarta up close. The city which is attached to the nickname as a city of culture, tourism city. And student city is supported by a culture of inhabitants who are always grateful and accept the nature that has been given by the Almighty, to the low cost of living. Yogyakarta has its own magnet as must-visit area ini Indonesia. The present of foreign culture ini Yogyakarta that is able to blend in with local culture ang grow and develop in the surrounding community, so it is not an exaggeration if Sri Sultan Hamengkubuwono X (Governor of DIY), said that “Yogyakarta is a miniatur of Indonesia”. The negative side of the presence of foreign culture to Ypgyakarta is the inability of local culture to blend in with the culture of immigants, which is precisely the diversity or plurality in Yogyakarta that can lead to conflict that lead to social unrest. Migrant communities who still bring the original culture of the region to Yogyakarta which may not necessarily be accept by culture of the people of Yogyakarta. There needs to be stategy from the Yogyakarta Regional Government in order to realize the values contained in Multiculturalism in the perspective of region resilience in Yogyakarta.